Irrigation Management by the "Tirtosari" Water User Farmer Association in Kesambirampak Village, Situbondo Regency - Ernawati, Ernawati; Yuswadi, Hary (Jurnal ENTITAS SOSIOLOGI, 2018)
Many factors drive the success of a food security program. One technical factor that strongly supports agricultural productivity is the availability of irrigation water suitable for crop needs. In this case, irrigation cannot be separated from Irrigation Services, Agricultural Services, and HIPPA. Initially, village irrigation management was carried out by an irrigation inspector named ulu-ulu, who was at the lowest level in the village organizational structure. In its implementation, village irrigation management faced many obstacles, causing gaps in water distribution. The purpose of this study is to analyze and describe the management of agricultural irrigation by HIPPA. This study uses qualitative methods, and the informants are determined using purposive techniques. From this study, it was found that many factors cause ineffectiveness in irrigation management. One of them is weak coordination in the HIPPA organization. It is even worse with the emergence of money politics in water distribution among farmers and water supervisors. Keywords: Irrigation management, Water User Farmer Association, farmer, irrigation service. Referensi: Cresswell, John W. 2016. Research Design Pendekatan Metode Kualitatif, Kuantitatif dan Campuran. Yogyakarta : Pustaka Pelajar. Duverger, Maurice.1998.Sosiologi Politik.Jakarta:RajaGrafindo Persada. E, Suzanne. 1996. Irigasi di Indonesia. Jakarta: Pustaka LP3ES. Ferystiawan, Mirza. 2010. Intervensi Penyuluh Pertanian Dalam Pemberdayaan Sosial Ekonomi Gabungan Kelompok Tani Di Asembagus.Universitas Jember. Skripsi . Fakultas Ilmu Sosial dan Politk. Jayanti,Nur.2006. Konflik antar Petani Pengguna Air Irigasi Sawah Pertanian di Desa Wongsorejo Kecamatan Wongsorejo Kabupaten Banyuwangi. Universitas Jember. Skripsi. Fakultas Ilmu Sosial dan Politik. Miles dan Hubeerman, A.M. 2014. Analisis Data Kualitatif. Bandung: PT Remaja Rosdakarya. Pasandaran, Efendi.1988.Irigasi Kelembagaan dan Ekonomi. Jakarta:PT.Gramedia. Pedoman Penulisan Karya Ilmiah.2017. Jember University. Pusposutardjo, Suprodjo.2001. Pengembagan Irigasi Usaha Tani Berkelanjutan dan Gerakan Hemat Air. Jakarta: Direktorat Jenderal Pendidikan Tinggi Departemen Pendidikan Nasional. Soekanto,Soerjono.2012.Sosiologi Suatu Pengantar. Jakarta: Rajawali Pers. Suratiyah,Ken. 2015. Ilmu Usaha Tani. Jakarta: Penebar Swadaya. Susan,Novri. 2009. Pengantar Sosiologi Konflik. Jakarta : Kencana. Syahyuti. 2006. Konsep Penting dalam Pembangunan dan pertanian. Jakarta Selatan: PT. Bina Rena Pariwara. Syahyuti, dkk. 2014. Organisasi Kesejahteraan Petani. Bogor : IPB Press. Yuswadi, Hary. 2005. Melawan Demi Kesejahteraan: Bentuk Perlawanan Petani Terhadap Kebijakan Pembangunan Pertanian. Jember: Kompyawisda Jatim. ---------------. 2001. Pengembangan Irigasi Usaha Tani Berkelanjutan. Yogyakarta: Direktorat Jenderal Pendidikan Tinggi Departemen Pendidikan Nasional